Evaluation of sires using univariate animal model in Murrah buffaloes - TEWARI, REETU; KUMAR, D; SINGH, C B; SINGH, HARPAL (The Indian Journal of Animal Sciences, 2021)
The percentage of sires superior to the population mean was 63.24, 58.82, and 60.29% using LS, BLUP, and DFREML method respectively for AFC trait. The corresponding figure in percentage applying LS, BLUP and DFREML methods were 51.47, 58.82 and 39.71% for FCI; 60.29, 47.06 and 47.06% for FLMY; 54.41, 64.71 and 42.65% for FLP; 51.47, 80.88 and 44.12% for WFC, and 51.47, 29.40 and 44.12% for FSP trait, respectively. The LS and BLUP methods gave almost the same results. This study concluded with the results that LS and BLUP method gave the same result for evaluating the different sires considering all the traits, viz. AFC, FCI, FLMY, FLP, WFC, and FSP. The values of lower error variance and high relative efficiency suggested that the BLUP method was best for evaluating the different sires followed by LS and DFREML methods using different first lactation traits.